A process of bonding between a lignocelluloses fiber and polymer. - Abdan, Khalina; Ibrahim, Nor Azowa; Md. Tahir, Paridah (2011)

(untitled)
A process for preparing a biocomposite material wherein the process comprises of the modification lignocelluloses fiber using monomer and alkaline treatment, additional anhydride group during blending and exposed to electron wave to produce active radicals. The process also involves blending the modified lignocelluloses fiber and modified polymer and adding a functionalized reactive additive to crosslink the said composite material.